Microfinance as an aspect of corporate enterprise development and its impact on SMME growth and local economic development in South Africa - Leeuw, Gladwyn Milano (My University, 2013)
Corporate enterprise development initiatives have emerged as a response to government policy that has enabled the core competencies and the business efficiency of the private sector to drive sustainable Small, Medium, Micro Enterprises (SMME) and local economic development (LED). This report describes the impact of a corporate enterprise development initiative that provides microfinance on SMME growth and LED. The secondary data utilised in this study was obtained from the Anglo American Zimele Community Fund database of 270 SMMEs that received unsecured enterprise development finance between 2007 and 2009 with an amortisation schedule longer than 12 months in various communities throughout South Africa. The study made use of quantitative research and in line with the primary objective to quantify the impact of microfinance on employment and turnover at the firm level and its subsequent impact on employment and turnover at the regional level; the research strategy used was quasi-experimental. It suggests that microfinance has had a positive influence on the entrepreneurial performance measured in terms of employment and turnover growth of SMMEs which results in LED in the communities where these businesses operate. Results also allude to the fact that this initiative could be the solution that facilitates the increase in economic growth and employment creation in South Africa.
Thesis (M.M. (Entrepreneurship and New Venture Creation))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.